High Figure-of-Merit Transparent Copper–Zinc Oxide Window Electrodes for Organic Photovoltaics - Pereira, H. Jessica; Hatton, Ross A. (Frontiers in Materials, 2019)
We report a copper - zinc oxide bilayer electrode supported on flexible polyethylene terephthalate (PET) with a sheet resistance of 11.3 Ω sq-1 and average transparency of 84.6 % in the wavelength range of 400 - 800 nm. The copper film is perforated with a dense array of sub-micron diameter apertures fabricated using polymer blend lithography, which imparts broad band anti-reflectivity. We demonstrate proof-of-principle that it is possible to fabricate the polymer mask by dip coating which is a scalable deposition method compatible with roll-to-roll processing. During storage of the electrode at ambient temperature the ZnO layer is spontaneously doped with copper from the underlying copper film and so the thin ZnO layer serves both as an anti-reflecting layer and an excellent electron transport layer. When compared with commercially available indium tin oxide coated (ITO) plastic substrates this electrode exhibits superior stability towards bending deformation, with no change in sheet resistance after bending through a 4 mm radius of curvature one hundred times. Model inverted organic photovoltaic (OPV) devices using this electrode exhibit a champion power conversion efficiency of 8.7%, which is the highest reported efficiency to date for an OPV using a copper based transparent electrode, outperforming identical devices using ITO coated plastic as the transparent electrode.